The global prevalence of major depressive disorder (MDD) among the elderly: a systematic review and meta-analysis - Abdoli, Nasrin; Salari, Nader; Darvishi, Niloofar; Jafarpour, Sima; Solaymani, Mina; Mohammadi, Masoud; Shohaimi, Shamarina (Elsevier, 2022)
Background: Major depressive disorder is characterized by a depressed mood or feeling of sadness, loss of interest or pleasure in everyday activities. Depressed individuals have a cognitive impairment, low self-esteem, difficulty making decisions, feeling helpless and hopeless. The factors that have been associated with depression include the lack of social support, living in rural areas, suffering from chronic diseases, smoking, and alcohol abuse. This study aimed to investigate the global prevalence of major depressive disorder in the elderly. Method: The electronic database such as Web of Science (WoS), Scopus, SID, PubMed, Google Scholar, Mag Iran, and IranDoc were systematically searched for studies reporting the prevalence of major depressive disorderin the elderly published up to March 2021. Meta-analysis was performed using Comprehensive Meta-Analysis (CMA) software. Heterogeneity between the studies was evaluated using the I2 index. Begg and Mazumdar rank correlation test was used to assess publication bias. Result: A total of 20 studies involving 18953 participants were included in this study. The global prevalence of major depression in the elderly was 13.3 % (95 % CI: 8.4–20.3 %). In the subgroup analysis, the prevalence of major depression in elderly women was 11.9 % (95 % CI: 7.6−18.6) and men 9.7 % (95 % CI: 5.2-17.3). No comparison was made between the two sexes, but based on the confidence intervals and large overlap, the two groups are not statistically different. Among continents, Australia had the highest prevalence of major depression in the elderly at 20.1 % (CI: 14.5-27.2 %). This was followed by Europe at 12.9 % (95 % CI: 5.1-28.9 %). Conclusion: Major depressive disorder has a growing trend in the elderly population of the world. The prevalence of major depression in the elderly depends on various clinical and demographic factors such as age and gender. Therefore, mental health and the quality of life (QoL) of the elderly are important. The present study emphasizes the importance of social support in mental health that can reduce depression in the elderly.